Longitudinal neuroimaging evaluation of the corticospinal tract in patients with stroke treated with autologous bone marrow cells. (10th March 2021) - Haque, Muhammad E.; Hasan, Khader M.; George, Sarah; Sitton, Clark; Boren, Seth; Arevalo, Octavio D.; Vahidy, Farhaan; Zhang, Xu; Cox, Charles S.; Alderman, Susan; Aronowski, Jaroslaw; Grotta, James C.; et al.
Abstract: Bone marrow mononuclear cells (MNCs) attenuate secondary degeneration and enhance recovery in stroke animal models. In a nonrandomized clinical trial, we imaged 37 patients with stroke: 17 patients treated with MNCs (treated) and 20 patients who received standard of care (nontreated) at 1, 3, and 12 months onset of stroke on 3.0T MRI system. Three‐dimensional anatomical and diffusion tensor images were obtained. The integrity of the corticospinal tract was assessed by measuring absolute and relative fractional anisotropy (FA) and mean diffusivity (MD) in the rostral pons (RP), posterior limb of the internal capsule, and corona radiata by drawing regions of interest. Infarct volume and stroke severity, which was assessed via the NIH Stroke Scale (NIHSS), were higher in the MNC group compared with the nontreated patients, which is a major limitation. Overall, the relative FA (rFA) of the nontreated patients exhibited continued reduction and an increase in relative MD (rMD) from 1 to 12 months, whereas despite larger infarcts and higher severity, treated patients displayed an increase in rFA from 3 to 12 months and no change in rMD. Contrary to the nontreated group, the treated patients' rFA was also significantly correlated ( P < .05) with NIHSS score in the RP at all time points, whereas rMD at the last two. Abstract : Autologous bone‐marrow mononuclear cells were intravenously administered in patients with acute ischemic stroke as procedure outline in panel (A). The nontreated patients were recruited separately. Both groups were imaged three times over year and neuroimaging biomarkers were developed. Integrity of the ipsilesional and contralesional cortical spinal tracts (CST) were evaluated via diffusion tensor imaging (DTI), in the rostral pons (RP), posterior limb of internal capsule (PLIC), and corona radiata (CR) as illustrated in panel (B). The relative fractional anisotropy (rFA), an imaging marker of white matter integrity, was serially quantified in these three regions in each group as shown in panel (C1), (C2), and (C3). Despite larger infarct size and severity of the treated group, the rFA either increased or stabilized as compared to the nontreated patients.